The Effect of Age Stereotype in Elderly Adults with the Mediation Role of Self-Esteem and Sense of Coherence - Rasool A; Abdullaeva B; Nazarov A; Kozokboeva D; Abdullaev R; Baydjanova I; Nuralieva N (Psychology Research and Behavior Management)
Abida Rasool,1 Barno Abdullaeva,2 Akmal Nazarov,3 Dilfuzakhon Kozokboeva,4 Rustam Abdullaev,5 Iroda Baydjanova,6 Nargiza Nuralieva7 1Smart Learning Institute of Beijing Normal University, Faculty of Education, Beijing Normal University, Beijing, 100082, People’s Republic of China; 2Scientific Work and Innovations, Tashkent State Pedagogical University Named After Nizami, Tashkent, 700135, Uzbekistan; 3Department of Psychology, Bukhara State University, Bukhara, 200100, Uzbekistan; 4Department of Integrated Course of Teaching English, Andijan State Institute of Foreign Languages, Andijan, 170100, Uzbekistan; 5Department of Physical Culture, Kokand State Pedagogical Institute, Fergana, 150700, Uzbekistan; 6Department of English Language and Literature, Urgench State University, Khorazm, 740000, Uzbekistan; 7School of Psychology, Shaanxi Normal University, Xian, 710062, People’s Republic of ChinaCorrespondence: Nargiza Nuralieva, Email nargizanuralieva@yahoo.com Barno Abdullaeva, Email barno-abdullaeva@bk.ruAbstract: This systematic review article considers the intertwinement of sense of coherence, self-esteem, and age stereotype among the heterogeneous aging population. Aging is multifaceted and complex, and older persons are a mosaic of values, experience, and psychological responses to society’s perception of their age. Underpinning this portrayal is the understanding that aging is not unidimensional but rather a complex aggregate of processes, challenges, and psychological processes. The first half describes the interdependence between age stereotypes and age discrimination and calls for the struggle against ageism at the social, institutional, and individual levels. The second half explores the influence of negative aging stereotypes on the self-concept of the elderly in Poland. It is necessary to investigate these processes to develop interventions and support systems suitable for the specific needs of the aging population. The third part deals with the complex cluster of self-concepts of self-esteem. The variability of self-esteem of the elderly ranging from high self-worth and confidence to low self-esteem and doubtfulness and low self-worth. Intervention must be specialized in trying to construct self-esteem, considering the variability of values of the elderly. In the fourth part, we deal with resilience continuum and the connection with age. Sense of coherence, a construct of Antonovsky’s psychology, is the centerpiece of resilience research on older individuals. Optimal sense of coherence enables individuals to manage old-age adversity and how lack of sense of coherence exposes them to the psychological impacts of stereotypes on old age. The dynamics of the aging population on the continuum, discussed in the problems of the fifth section, illustrate the response to age stereotypes and resilience and how these affect overall well-being.Keywords: age stereotypes, coherence, aging, resilience, positive narratives